Association between dietary intake of flavonoids and chronic low back pain: a cross-sectional study - Zhou, Haibin; Xi, Yang; Gao, Sizhe; Zhou, Yan (Frontiers in Nutrition, 2024)
The purpose of this study was to explore the association between flavonoids intake and chronic low back pain (CLBP).Methods: This cross-sectional study analyzed data from the National Health and Nutrition Examination Survey. Dietary flavonoids intake was assessed using a two-day recall questionnaire on dietary intake. CLBP was defined based of self-reported question. Weighted univariate and multivariate logistic regression models were performed to evaluate the relationship between flavonoids intake and CLBP.Additionally, subgroup analyses were conducted based on age, sedentary behavior time, arthritis, depression, and sleep disorder.Results: A total of 3,136 adults were included, and 460 participants developed CLBP.After adjusting confounders, compared with the lowest total flavonoids intake tertile (reference group), flavonoids intake with highest tertile (>170 mg) was associated with reduced odds of CLBP [odds ratio (OR) =0.74, 95% confidence interval (CI): 0.57-0.95]. This relationship of flavonoids intake with CLBP remained statistically significant among participants aged ≥45 years (OR=0.52, 95%CI: 0.35-0.76), with sedentary behavior time of >3h (OR=0.60, 95%CI: 0.41-0.86), with arthritis (OR=0.51, 95%CI: 0.29-0.90), depression (OR=0.48, 95%CI: 0.24-0.98), and sleep disorder (OR=0.27, 95%CI: 0.12-0.60).Higher flavonoids intake was found to be negatively associated with the likelihood of CLBP. For the general adult population, consuming foods rich in flavonoids may be linked to a reduced risk of CLBP.